GUAR GUM ADDITION ON PHYSICAL CHARACTERISTICS OF EXTRUDED DRY CORN NOODLE FROM MIXTURE OF WET AND DRY CORN FLOURS - Aminullah, Aminullah; Muhandri, Tjahja; Subarna, Subarna (Jurnal Pertanian, 2020)
The drying process of corn noodles was an effort to increase the shelf life and it was a form of noodles diversification. The objective of this research was to study and analyze the effect of guar gum addition on the physical quality of the extruded dry corn noodle made from a mixture of wet and dry corn flour. Manufacturing dry corn noodles was conducted using wet corn noodles from a mixture of wet and dry corn flour, which was then dried in a tray dryer at a temperature of 60-70 °C for 1 - 1.5 hours. The treatments used were a combination of alum levels of 0.01%; moisture content of 80% (dry base); and guar gum concentration of 0%, 1%, and 2%. Physical properties of dry corn noodles included rehydration time, hardness, adhesiveness, suppleness, elongation, and cooking loss. The results showed that the optimum rehydration time for dry corn noodles was about 9 minutes. The addition of guar gum to the physical qualities of dry corn noodles tended not to be significant statistically, but as a score, an increase in guar gum levels tended to increase the elongation of dry corn noodles. While, increasing levels of guar gum tended to reduce the stickiness and cooking loss levels of them.